Plagiarism in the era of new technologies (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The impact of the new technologies on our daily life has arrived like an uncontrolled tsunami at the traditional systems of intellectual property, which were not prepared at all to answer to new situations and conflicts to date not known. The new techniques of creation and exploitation of works, as well as the easy and economic access to the Internet for everyone that wishes to use it, has made proliferate with multiplying effect all these new problems. As In which regards to the plagiarism, it is clear for anyone that, nowadays, is easier than ever to plagiarize without punish other people’s work, in almost all the sorts and categories of works. In this article, we will first comment the legal and scholar frame of the plagiarism, in its more traditional conception, discussing later in detail how this legal construction can or cannot adapt to the new plagiarizing conducts derived from the use of the new technologies.
Keywords: plagio; nuevas tecnologías; copia; usurpación; autoría.